The philosophy of taxation and public finance - a McGee, Robert W. (Kluwer Academic Publishers, 2004)
Most public finance books are texts, which are aimed at undergraduate or graduate students. They are overly technical in nature and appeal only to a narrow range of bureaucrats and academics. Books on taxation are written for tax practitioners and usually emphasize either what the law is or how to maneuver through the labyrinth of tax law to minimize taxes for clients. Philosophy books on taxation or public finance simply do not exist. The Philosophy of Taxation and Public Finance is different. It is written in nontechnical language and is aimed to appeal to a wide range of readers, including practitioners, academics and students in the fields of taxation, public finance, economics, law, philosophy and political science as well as general readers who are interested in learning why they are being taxed the way they are. The author addresses the major issues and topics in taxation and public finance and injects them with philosophical insights. He discusses questions such as: + What arguments have been used to justify taxation? + When is tax evasion unethical? + Are some taxes better than others? + What are the proper functions of government? + How much is enough? + Is the ability to pay concept valid? + When can punitive taxes be justified?